Distribution of alpha-actinin-3 rs1815739 and angiotensin-1 converting enzyme InDel polymorphisms in Turkish bodybuilders - ULUCAN, KORKUT (SPANDIDOS PUBL LTD, 2020)
The determination of the genetic profiles of successful athletes and the effects of these genetic parameters on athletic performance is gaining increasing interest. The majority of studies assessing the genetics of athletes usually analyse the most well-known genetic variations in athletes associated with the different specialties. The aim of the present study was to analyse the ACE InDel and ACTN3 rs1815739 polymorphisms in Turkish bodybuilders. A total of 11 male bodybuilders were recruited and genotyped for these polymorphisms. The respective percentage of the ACE II, ID and DD genotypes were 18, 73 and 9. For the ACTN3 genotype, the respective frequencies were 55 and 45 for the RX and RR genotypes. No XX genotype was detected. The allelic counts were 12 (55%) for I and 10 (45%) for the D alleles of ACE; and 12 (55%) and 10 (45%) for R and X alleles, respectively, for the ACTN3 genotype. Additionally, 5 athletes had ID + RX genotypes in terms of ACE InDel and ACTN3 rs1815739 polymorphisms, respectively. These results indicate the importance of endurance related alleles of ACE and ACTN3 in bodybuilders. The results of the present are in agreement with previous studies, highlighting a potential association between specific polymorphisms and the endurance-related nature of bodybuilders. Further studies with larger cohorts are required to understand the association between these polymorphisms and specific parameters performance in bodybuilders.
Keywords: genetics; polymorphisms; sports genetics; bodybuilder; single nucleotide polymorphism; fitness; ACTN3 GENOTYPE; GENE